Isopoliteia in Hellenistic Times - Saba, Sara, (Brill Studies in Greek and Roman Epigraphy;, 2020)
The diplomatic tool known as isopolity is a testament to Greek ingenuity and is attested all over the Mediterranean from the 4th to 1st century B.C., mainly epigraphically. "Isopoliteia" was a popular way to establish new relashionships, reinforce old ones or to regulate difficult situations among communities in the Hellenistic Period. This book offers close scrutiny of potential citizenship between communities as well as a fresh examination of new evidence which has emerged since the publication of the only monograph written on the topic by Wilfried Gawantka in 1975. The book brings together all the evidence for isopolity in the Hellenistic world and demonstrates that communities used this diplomatic tool across different kinds of agreements and through a range of different ways.